2020
DOI: 10.11591/ijphs.v9i1.14896
|View full text |Cite
|
Sign up to set email alerts
|

Health seeking behavior in Bulak Banteng, Surabaya

Abstract: Infant and under-five mortality rate in the world is still a major health problem that must be resolved immediately. Mother’s health seeking behavior very important to manage the health of his children. Purpose of this study was to investigate health seeking behavior among mothers when their children were sick. This study was descriptive quantitative involved 50 respondents. The results show majority mothers choose to take action when their children are sick with most choosing to take them to health care facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
1
1
1
2
Order By: Relevance
“…12 Another study about mother's health seeking behavior in Surabaya, Indonesia, it concluded that if the level of parental education is high hence the level of understanding will be high and certainly include more knowledge about how to care when the child is in an unhealthy condition. 14,18 This is in accordance with our study where higher education in mothers shows a better understanding when their children need cancer treatment that they keep bring their children for treatment so their children do not abandon the treatment.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…12 Another study about mother's health seeking behavior in Surabaya, Indonesia, it concluded that if the level of parental education is high hence the level of understanding will be high and certainly include more knowledge about how to care when the child is in an unhealthy condition. 14,18 This is in accordance with our study where higher education in mothers shows a better understanding when their children need cancer treatment that they keep bring their children for treatment so their children do not abandon the treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Although insignificant, it was also found that patients whose parents have poor attitudes and behavior related to COVID-19 infection also has an increased rate of abandonment. Previous research among childhood cancer reported that financial burden is the major cause of treatment abandonment, 12 - 14 however our study shows the correlation between socioeconomic impact with abandonment rate of treatment is insignificant. In addition, the difference in COVID-19 knowledge and social support were not significantly related ( Table 3 ).…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…Berdasarkan penelitian yang dilakukan di Puskesmas Bulak Banteng, mayoritas Ibu memilih untuk melakukan tindakan/pengobatan sendiri ketika anaknya sakit dengan sebagian besar memilih untuk membawa mereka ke fasilitas pelayanan 5 . Dari penelitian lain juga menunjukkan, pengetahuan ibu tentang gejala penyakit bayi baru lahir dan bayi muda, yang merupakan salah satu faktor penting yang mempengaruhi perilaku mencari perawatan, dan kurang dari dari 50% ibu memiliki pengetahuan yang cukup tentang penyakit bayi baru lahir dan bayi muda 6 .…”
Section: Pendahuluanunclassified
“…Berdasarkan penelitian yang dilakukan di Puskesmas Bulak Banteng, mayoritas Ibu memilih untuk melakukan tindakan/pengobatan sendiri ketika anaknya sakit dengan sebagian besar memilih untuk membawa mereka ke fasilitas pelayanan 5 . Penelitian yang dilakukan Thakur, dkk, ditemukan terdapat korelasi sikap ibu mengenai tanda-tanda bahaya neonatus dan tingkat praktiknya , dapat diartikan jika sikap positif ibu nifas meningkat, praktik ibu nifas terhadap tanda bahaya neonatus juga meningkat Bayi yang lahir di fasilitas kesehatan seharusnya dipulangkan minimal 24 jam setelah lahir apabila selama pengawasan tidak dijumpai kelainan.…”
Section: Hasil Dan Pembahasanunclassified